A review on the socio-environmental impacts of lithium supply for electric aircraft - Chen-Glasser, Melodie; DeCaluwe, Steven C. (Frontiers in Aerospace Engineering, 2022)
Electrified aircraft have gained traction as a promising approach to emissions abatement in the aviation sector. This transition will require overcoming numerous technical challenges related to increasing battery energy density, as well as logistic challenges related to the lithium supply chain, which is already stressed due to high demand for electric vehicles. We have estimated that lithium demand for electrified aviation may raise lithium demand in the range of 10-250%. The uncertainty in these estimates show the importance of quantifying the impacts of electrified aviation and designing batteries to mitigate additional demand. In addition, most reviews on electrified aviation do not include information on the localized social and environmental impacts caused by lithium demand, despite their importance to enabling technology necessary for emissions reductions. This review seeks to fill this gap by presenting an overview of environmental and social research in context with one another to encourage researchers in the field to consider these dynamics as part of electrified aircraft design. Given that the high energy density batteries necessary to enable large-scale electrification of aircraft are still under development, continued progress in this field should emphasize sustainable governance for lithium extraction and a circular battery economy to reduce social and environmental stressors.